Effect of Fiber on Improvement of Flextural Strength of Acrylic Resin Immersed in Sodium Hypochlorite - B Ebadian; M Bonyadi; F Bajgholi (Isfahan University of Medical Sciences, 2007)
Introduction: Flexural strength of denture base acrylic resin may be affected during disinfection process. The fibers are used as strengthening methods. The aim of this study was evaluation of fiber reinforced and non reinforced heat cure acrylic resin samples immersed in sodium hypochlorite 2.5% solution.Methods and Materials: Sixty acrylic samples (3×10×65mm) were made. Thirty samples reinforced with a non impregnated fiber. The fibers were positioned, 1mm below the surface of samples. The groups were divided to three groups: 1-without immersion, 2-immersed in water for 8 hours, 3-immersed in sodium hypochlorite 2.5% for 8 hours. Flexural strength of samples was evaluated by 3-point bending test. The results were analyzed with Two Way ANOVA Test.Results: Mean flexural strength of fiber reinforced samples immersed in disinfectant solution was 126.5 Mpa, and in non reinforced samples immersed in disinfectant solution was 122.7Mpa. Mean flexural strength of all groups had no significant differences.Conclusion: The results showed this kind of fiber can not increase the flexural strength of acrylic resin samples. This method is not effective in strengthening of heat cure acrylic resin in dry, wet condition and immersed in sodium hypochlorite solution.Key words: Acrylic resin, Disinfection, Fiber, Flexural strength, Denture base.